Catálogo y registro del repertorio musical patrimonial existente en el Archivo del Museo de la Música “Salvador Zaragocín Tapia” a través del Sistema de Información del Patrimonio Cultural del Ecuador (SIPCE) - Vivanco Pinta, Karol Mishell (2023)
The musical heritage repertoire housed in the "Salvador Zaragocín Tapia" Music Museum represents an important source of information on which the musical identity of the city has been built. Therefore, it is essential to develop activities related to heritage preservation. In the present work of curricular integration, the use of strategies for the protection of the musical heritage allowed the creation of a catalogue with the patrimonial documentation that rests in the archive rooms of the music museum; this constitutes a complete tool in terms of ordering and registration. The methodology was oriented to describe, understand, and interpret the reality of the musical documents of the archive in question through the non-experimental transectional design. Likewise, the information collected in the results allowed us to identify the archival description strategies used in the repository, which correspond to the usage of the index as a registration instrument for the patrimonial information stored in it. However, the index is not a complete information recording tool, it is generally used to support other instruments. Therefore, the expansion of this index through a catalogue, contributes to the preservation of heritage through its dissemination. Keywords: musical heritage, catalogue, archiving.